The Effects of Problem-based Learning in Students Reading Comprehension for Mastering the Content and Vocabulary Acquisition - Hazwani Sidik; Alias Masek (Universitas Pendidikan Indonesia (UPI), 2021)
English reading comprehension is the most crucial language abilities in colleges where English is learned as a second language. A vigorous and powerful reading ability is certainly crucial in primary studies for students to accomplish in advanced education. However, the method in which they are instructed through lecture and paper pencil’s method were less relevant and effective in 21st Century. Students become passive, demotivated, bored, and feeling shy by the conventional teaching and learning. The purpose of this study is to examine the effectiveness of problem-based learning (PBL) on student’s English reading comprehension for mastering the contents and vocabulary acquisition. The study used a quantitative data where using an experimental pre-posttest design and the independent t-test and one-way ANOVA has been performed to test the hypothesis of the studies. The result indicated that there were statistically significant differences between the experimental and control groups for student’s reading comprehension for mastering the content and vocabulary acquisition using PBL. The results showed that the students who received PBL learning approached achieved higher performance outcome than student who is not received the PBL approach